A pilot feasibility study of Conexiones, a telephone-delivered cancer parenting education program for Hispanic mothers. Issue 1 (2nd January 2023) - Palacios, Rebecca; Lewis, Frances Marcus; Reyes, Clara Lucia; Griffith, Kristin; Zahlis, Ellen; Shands, Mary Ellen
Abstract: Objective: To test the short-term impact of Conexiones, a culturally adapted cancer parenting education program for diagnosed child-rearing Hispanic mothers. Design: Single group, pre-post-test design. Sample: 18 U.S. Hispanic mothers diagnosed within 2 years with early-stage cancer (0–III) raising a child (5–17 years). Methods: Participants completed consent, baseline measures, and five telephone-delivered Conexiones sessions at 2-week intervals from trained patient educators in English or Spanish. Outcomes were assessed at baseline and at 3 months. Results: Maternal depressed mood, parenting self-efficacy, and parenting quality significantly improved. Children's anxious/depressed mood tended to significantly improve. Outcomes did not co-vary with mothers' level of acculturation. Conclusions: Conexiones appears to positively improve Hispanic mothers' distress and parenting competencies; efficacy testing is warranted within a larger randomized control trial. Implications for Psychosocial Providers: A brief, culturally adapted cancer parenting education program has potential to enhance Hispanic mothers' and children's behavioral-emotional adjustment to a mother's cancer.